Pengaruh Air Kelapa dan Cucian Beras terhadap Pertumbuhan Jamur Tiram - Rukmi Budirahaju; Mahindra Dewi Nur Aisyah; Torikul Mutoharoh (Universitas Darul Ulum, 2023)
The increasing demand for oyster mushrooms requires innovative approaches to increase their production. Traditional cultivation methods often face challenges, particularly in the slow growth of mycelium, which can take 40-60 days. Previous studies have not extensively explored the synergistic effects of natural growth enhancers such as coconut water and rice washing on mycelium development. This study addresses this gap by investigating the impact of these organic substances on the growth of Pleurotus ostreatus (oyster mushroom).The novelty of this study lies in its focus on utilizing coconut water, which is rich in nutrients and growth hormones, together with rice washing, which contains essential vitamins and minerals, to optimize mycelium growth. The findings showed that the optimal pH for mycelium growth is 4, and the specific combination of coconut water and rice washing significantly increased mycelium spread. The benefits of this study go beyond academic knowledge; it provides practical solutions for mushroom farmers who want to increase yields and reduce cultivation time. By demonstrating the effectiveness of these natural growth enhancers, this study contributes to sustainable agricultural practices and offers a cost-effective alternative to chemical fertilizers. The excellence of this paper is emphasized by its comprehensive analysis and its potential real-world application in mushroom cultivation, which ultimately supports food security and economic development in the agricultural sector